Modified Fluid Gelatin Versus Crystalloids in CABG Surgery Patients: a Propensity Score Matched Analysis - V. V. Bazylev; A. I. Magilevetz; A. A. Schegolkov; A. V. Bulygin (Вестник анестезиологии и реаниматологии)
The objective: to compare efficacy and safety of infusion therapy with modified fluid gelatin (MFG) and balanced salt solutions.Subjects and Methods. 1,820 patients after coronary artery bypass grafting were enrolled in the retrospective study. Two groups of 362 patients were formed by the matching index method.Results. Primary endpoints. Acute kidney injury (AKI) developed less frequently in the crystalloid group compared to the colloid group, also more patients in the colloid group received fresh frozen plasma and red blood cells.In the crystalloid group, the duration of stay in the intensive care unit (ICU) decreased, while the duration of mechanical ventilation increased. The use of MFG within infusion therapy made it possible to reduce the volume of balanced salt solutions transfused both in the perioperative period and during stay in the intensive care unit. However, there was no intergroup difference in the total volume of infusion therapy calculated based on the patient's actual weight.Conclusions. The use of MFG as part of infusion therapy may increase the incidence of AKI, the need for transfusion of blood components, as well as the duration of stay in ICU. Use of MFG was associated with shorter duration of mechanical ventilation.